2013
DOI: 10.1097/opx.0b013e318296befe
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Corneal Asphericity (Q Value) Between African-Americans and Whites

Abstract: Corneal asphericity as represented by mean Q value varies significantly between African-Americans and whites. The greatest differences are evident in opposing quadrants and appear to be little influenced by age, gender, or SE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 32 publications
3
29
2
Order By: Relevance
“…Sheridan and Douthwaite 5 assessed asphericity in terms of shape factor in nasal and temporal hemi-meridians and showed that the nasal cornea flattened at a faster rate than the temporal cornea with respect to geometric center. Recent studies that investigated hemi-meridional Q values in different ethnicities have also showed a similar trend, 8,13 where the corneal asphericity in the nasal and superior hemi-meridians was more prolate than the temporal and inferior hemi-meridians, respectively.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Sheridan and Douthwaite 5 assessed asphericity in terms of shape factor in nasal and temporal hemi-meridians and showed that the nasal cornea flattened at a faster rate than the temporal cornea with respect to geometric center. Recent studies that investigated hemi-meridional Q values in different ethnicities have also showed a similar trend, 8,13 where the corneal asphericity in the nasal and superior hemi-meridians was more prolate than the temporal and inferior hemi-meridians, respectively.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have limited their investigation to only a few meridians 4,7 or hemi-meridians. 2,5,8,13 The current study gives a much broader view of corneal shape as it has investigated corneal shape in sectors encompassing the entire cornea over the central 8-mm zone. This study has shown that for eyes with up to 1.50 diopters of corneal toricity, the corneal shape is not uniform in terms of asphericity in different corneal sectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myopes were more oblate and hyperopes were more prolate [20,21]. Contrasting these results, some studies show no significant correlation between corneal surface asphericity and spherical equivalence [22,23].…”
Section: Discussionmentioning
confidence: 91%
“…In our population, the SD in the preoperative Q value was 0.12, which closely models reported values from other studies. 19 The reported difference in DQ/D between both lasers was only 0.02, which is unlikely to be clinically significant. Additionally, because we have no data for the Allegretto laser beyond 25.00 D, it is difficult to conclude whether the VISX laser has a smaller for treatments beyond 24.05 D. For this reason, we report the population average DQ/D as most representative of the data gathered.…”
Section: Discussionmentioning
confidence: 96%